Reader Response: Association of Loneliness With 10-Year Dementia Risk and Early Markers of Vulnerability for Neurocognitive Decline. (13th September 2022) - Daly, Timothy
Abstract : There are striking parallels between the recent finding of Salinas and colleagues that older adults who described feeling lonely 3 or more days a week had a greater 10-year risk of developing dementia 1 and the report by Wallace et al. 2 of a strong 10-year link between frailty and increased dementia risk. In other words, research shows that individuals with dementia tend to have been lonely or frail in the decade before developing the condition.